Analisis non-linier elemen hingga struktur balok beton prategang dua bentangan - AL FARIDI, Salahuddin ([Yogyakarta] : Universitas Gadjah Mada, 2010)
Two-span prestressed concrete beams normally will not fail when the moment capacity of just one critical section is reached. A plastic hinge will form at that section, permitting large rotation to occur and thus transferring load to other locations along the span where the moment capacity has not yet been reached. Beside experimental, research can be held by using non-linear finite element analysis. This research was conducted to study the flexural behavior of two-span prestressed concrete beams based on non-linear finite element analysis. In this research nine numerical models of two-span prestressed concrete beams were made and consist of: 1) three experimental beams (BC1, BC2, BC3) with cross sectional dimension of 150 mm x 300 mm and 3000 mm long each span as referred by Bishara and Brar (1974) as quoted by Rebentros (2003); 2) three rectangular beams (BP-R0, BP-R1, BP-R2); and 3) three tee beams (BT-R0, BT-R1, BT-R2). Each rectangular and tee beams were of equal cross section and span length but vary in tensile reinforcement at interior support. Numerical models of the experimental beams were analyzed by non-linear finite element method using ANSYS and ATENA software. Result of the analysis was calibrated against experimental results from Bishara and Brar (1974) in Rebentros (2003). Once validated, the models were re-analyzed with the variation of concrete strength and As,mid/As,sup. Further, numerical models of rectangular and tee beams were analyzed to examine the load-deflection relationship, stiffness, ductility, crack pattern, load-moment relationship and moment redistribution. Result of the research shows that two-span prestressed concrete beams can be well modeled using ANSYS and ATENA. The differences of ultimate load strength between ANSYS and experimental result by Bishara and Brar for BC1, BC2 and BC3 were 0.51%, 1.04% and 0%, and for ATENA were 2.56%, 0.52% and 0.52%. The differences of stiffness between ANSYS and experimental result were 146.11%, 54.23% and 18.52%, and for ATENA were 188.61%, 81.95% and 40.17%. The differences of ductility between ANSYS and experimental result were 143.97%, 24% and 25.06%, and for ATENA were 154.72%, 58.66% and 12.02%. The ultimate load strength of ANSYS for rectangular and tee beams were greater than ATENA, for BP-R0, BP-R1, BP-R2, BT-R0, BT-R1 and BT-R2 were 5.37%, 5.95%, 6.59%, 3.06%, 3.09% and 4.17% respectively. The stiffness of ANSYS were smaller 3.36%, 3.44%, 3.51%, 12.34%, 11.5% and 11.51% than ATENA. The ductility of ANSYS were smaller 18.55%, 30.38%, 27.15%, 5.35%, 7.04% and 8.15% than ATENA. Crack pattern for all beams shows that the beams fail in flexure. The load-moment relationship shows that moment redistribution begins after the formation of the first crack. The value of moment redistribution were highly influenced by As,sup/As,mid. Moment redistribution increases with the decrease of As,sup/As,mid.